Iowa CBC reporting form, Alleman, December 29, 1985 - Mosman, Deanet al (1985)
Checklist dated December 29, 1985 compiled by Dean Mosman. A list of birds sighted by Mosman and two others around Alleman. A total of 30 species and 1,080 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed